2018
DOI: 10.1002/ece3.4724
|View full text |Cite
|
Sign up to set email alerts
|

Highly flexible infection programs in a specialized wheat pathogen

Abstract: Many filamentous plant pathogens exhibit high levels of genomic variability, yet the impact of this variation on host–pathogen interactions is largely unknown. We have addressed host specialization in the wheat pathogen Zymoseptoria tritici. Our study builds on comparative analyses of infection and gene expression phenotypes of three isolates and reveals the extent to which genomic variation translates into phenotypic variation. The isolates exhibit genetic and genomic variation but are similarly virulent. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
171
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(201 citation statements)
references
References 87 publications
10
171
0
Order By: Relevance
“…a). In contrast, Z. tritici successfully infected and colonized the mesophyll tissue of the susceptible wheat cultivar Obelisk during different infection stages, as already described in detail (Haueisen et al , ). Penetration of leaf stomata at 4 dpi was followed by the establishment of a hyphal network in the mesophyll tissue until 7–11 dpi and subsequently the switch to necrotrophy when biomass increased substantially, resulting in the formation of pycnidia (Fig.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…a). In contrast, Z. tritici successfully infected and colonized the mesophyll tissue of the susceptible wheat cultivar Obelisk during different infection stages, as already described in detail (Haueisen et al , ). Penetration of leaf stomata at 4 dpi was followed by the establishment of a hyphal network in the mesophyll tissue until 7–11 dpi and subsequently the switch to necrotrophy when biomass increased substantially, resulting in the formation of pycnidia (Fig.…”
Section: Resultssupporting
confidence: 60%
“…Data from Haueisen et al . (). (d) In planta expression of Zt107320 is displayed relative to expression during axenic growth.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed our results confirmed that a large region of 800kb on the chromosome 7 is without any transcriptional activity ( Additional file 3: Figure S5 ). This feature was already mentioned for the strain IPO-323 by (Rudd et al 2015; Schotanus et al 2015; and Haueisen et al 2019). This chromosomal region is marked with histone H3K27me3 modifications that mediate transcriptional silencing, and these epigenetic marks are similar to the marks already identified on ACs.…”
Section: Resultssupporting
confidence: 66%